2011
DOI: 10.1590/s0101-20612011000400020
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids profile of pulp and nuts of Brazilian fruits

Abstract: ResumoFrutas e castanhas das regiões Norte e Nordeste do Brasil foram coletadas para determinação da composição em ácidos graxos do óleo da polpa e da castanha. As espécies estudadas foram castanha-do-pará (Bertholletia excelsa H.B.K.), mucajá (Coumarigida M.), inajá (Maximilianamaripa D.), jenipapo (Genipa Americana L.) e buriti (Mauritia flexuosa L.). Os ésteres metílicos de ácidos graxos foram analisados por cromatografia gasosa com detector por ionização em chama (GC-FID). O ácido graxo majoritário da cast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
1
8
1
2
Order By: Relevance
“…The Amazon buriti presented the lowest saturated fatty acid contents. These values were lower than the ones reported by Costa et al (2011) in the study of fatty acid contents of Brazilian nuts and fruit pulps and seeds. Dn the other hand, they presented the highest contents of monounsaturated fatty acids, similar to what has been reported in the literature (76.0 g/100 g), for fruits from the same region (Darnet et al, 2011).…”
Section: Fatty Acid Compositioncontrasting
confidence: 79%
“…The Amazon buriti presented the lowest saturated fatty acid contents. These values were lower than the ones reported by Costa et al (2011) in the study of fatty acid contents of Brazilian nuts and fruit pulps and seeds. Dn the other hand, they presented the highest contents of monounsaturated fatty acids, similar to what has been reported in the literature (76.0 g/100 g), for fruits from the same region (Darnet et al, 2011).…”
Section: Fatty Acid Compositioncontrasting
confidence: 79%
“…In folk medicine, leaves, bark, fruits and roots are employed, usually in the form of teas; in addition to medicinal use, it has food, dyeing and ornamental purposes (Souza et al, 2013). The usefulness of this species is a function of its chemical composition, mainly composed of iridoids such as genipin and geniposide (Alves et al, 2017), steroids (Conceição et al, 2011), fatty acids (Costa et al, 2011) and tannins (Moura et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among unsaturated fatty acids in buriti oil, oleic acid (C18: 1ω9C) is reported in large quantities (SILVA et al, 2009;COSTA et al, 2011;AQUINO et al, 2012;FREITAS et al, 2017). SILVA et al (2009) found that triacylglycerols account for 91.9 % of constituents present in buriti oil, whereas free fatty acids constituted just 3.1 %.…”
Section: Food Technologymentioning
confidence: 99%